Disorder affects judgements about a neighbourhood: police presence does not - Hill, Jessica; Pollet, Thomas V.; Nettle, Daniel (PeerJ, 2014)
Many police forces operate a policy of high visibility in disordered neighbourhoods with high crime. However, little is known about whether increased police presence influences people’s beliefs about a neighbourhood’s social environment or their fear of crime. Three experimental studies compared people’s perceptions of social capital and fear of crime in disordered and ordered neighbourhoods, either with a police presence or no police presence. In all studies, neighbourhood disorder lowered perceptions of social capital, resulting in a higher fear of crime. Police presence or absence had no significant effect. The pervasive effects of disorder above other environmental cues are discussed.
Keywords: Social capital; Police visibility; Disorder; Fear of crime